The Historical Geography of Gordyene. Part II: Oriental Sources - Marciak, Michał (Anabasis. Studia Classica et Orientalia, 2013)
This article discusses Oriental sources containing geographical and ethnographical information about Gordyene. The study makes the case (following great linguists such as F.C. Andreas, T. Nöldeke, V. Minorsky) that the forms Korčēk‘, Korčayk‘ and Kordik‘ are not linguistically akin to the root Qardū. As a result, the Armenian sources with information about Korčēk‘, Korčayk‘, Kordrik‘ rather mirror the expansion of the post-Cyrti or proto-Kurdish tribes than directly contribute to our knowledge about Gordyene (Korduk‘). Furthermore, it is argued that the location of Noah’s Ark in the mountains of Qardū (modern Cudi Dağɩ) known to Jewish, Syriac and Islamic traditions can be used to interpret the data from Josephus’ Ant. 20:24, and consequently to precisely locate the first century CE expansion of Adiabene into Gordyene: it reached at least as far as Cizre. Literary evidence obtained from Oriental sources supplements our knowledge on Gordyene’s culture – it included Iranian, Armenian, Semitic and Greek elements. What is more, in the light of Talmudic references, Gordyene again appears to have been a “proverbially wealthy” country.